MENINGKATKAN AKTIVITAS, KERJA SAMA, DAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN POLA DI SEKOLAH DASAR - Nisa, Khairun; Jannah, Fathul; Agusta, Akhmad Riandy; Hidayat, Ari (Universitas Negeri Medan, 2024)
Abstract: The problem in this study is the low activity, cooperation and learning outcomes of students in mathematics learning. The purpose of the study is to describe the activities of educators and analyze the increase in activity, cooperation and learning outcomes of students. This type of research is PTK implemented in 4 meetings. The subjects of the study were grade V students of SDN Antasan Besar 1. Using qualitative and quantitative data types. The results showed that educator activity increased to a score of 40 with the criteria of